(untitled) (Mustansiria Dental Journal, 2024)
Deep margin elevation (DME) is considered a conservative approach for restoring the deep proximal margin by applying resin composite increments over the preexisting cervical margin to relocate it coronally and facilitate the insertion of indirect restoration. Different materials have been applied in DME. Materials and methods: An analysis of the research publications in the literature dealing with the different restorative materials used for DME regarding their fracture resistance, microleakage, marginal quality, and marginal adaptation that have been published from 2000 until 2023 using MEDLINE (PubMed) and Google Scholar databases.Results. The studies showed that enamel margin had the best gap-free margins, followed by direct bonding to dentine, DME required careful layering of 1 mm increment to show fewer gaps, and there was no significant difference compared with those without margin elevation. DME didn’t significantly influence the fracture strength in all of the materials utilized for DME except that elevated with bulk-fill Smart Dentin Replacement.Conclusions: This review included 16 in vitro studies concerning the different restorative materials used for DME. The samples in multiple layers of 1 mm increment of DME showed similar results to those where the indirect restorations bonded directly to dentine. On the other hand, in clinical practice, DME assists in making indirect restoration cementation easier, faster, and more reliable. Therefore, further research and clinical observations are needed.